2012
DOI: 10.1039/c2mb25208b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the production of tropane alkaloids in transgenic Anisodus acutangulus hairy root cultures by over-expressing tropinone reductase I and hyoscyamine-6β-hydroxylase

Abstract: Tropane alkaloids (TA) including hyoscyamine, anisodamine, scopolamine and anisodine, are used medicinally as anticholinergic agents with increasing market demand, so it is very important to improve TA production by metabolic engineering strategy. Here, we report the simultaneous introduction of genes encoding the branch-controlling enzyme tropinone reductase I (TRI, EU424321) and the downstream rate-limiting enzyme hyoscyamine-6β-hydroxylase (H6H, EF187826) involved in TA biosynthesis into Anisodus acutangulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…There are a lot of successful cases in this field. In A. belladonna and A. acutangulus , biosynthesis of scopolamine was dramatically enhanced by overexpressing the committed enzymes, H6H and TRI in A. annua , the production of artemisinin was greatly promoted by overexpressing CYP71AV1 and aldehyde 11Δ(13) reductase ; in Catharanthus roseus , overexpressing strictosidine synthase led to the increased production of ajmalicine ; in Ophiorrhiza pumila , the anti‐cancer camptothecin was significantly improved by overexpressing geraniol‐10‐hydroxylase and strictosidine synthase ; in Salvia miltiorrhiza , biosynthesis of tanshinone was enhanced by different combination of the key enzymes . These cases strongly suggest that overexpression of key enzymes is a very potent tool for genetic improvement of metabolite biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…There are a lot of successful cases in this field. In A. belladonna and A. acutangulus , biosynthesis of scopolamine was dramatically enhanced by overexpressing the committed enzymes, H6H and TRI in A. annua , the production of artemisinin was greatly promoted by overexpressing CYP71AV1 and aldehyde 11Δ(13) reductase ; in Catharanthus roseus , overexpressing strictosidine synthase led to the increased production of ajmalicine ; in Ophiorrhiza pumila , the anti‐cancer camptothecin was significantly improved by overexpressing geraniol‐10‐hydroxylase and strictosidine synthase ; in Salvia miltiorrhiza , biosynthesis of tanshinone was enhanced by different combination of the key enzymes . These cases strongly suggest that overexpression of key enzymes is a very potent tool for genetic improvement of metabolite biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to producing defensive responses, elicitation can induce the accumulation of secondary metabolites, including tropane alkaloids [44]. Elicitation with ZnO caused an increase in hyoscyamine and scopolamine content at all exposure times compared to the control hairy roots, although the maximum level of alkaloids was detected with 100 mg/L ZnO.…”
Section: Discussionmentioning
confidence: 96%
“…Suppression of SlTRII has been used as an alternative method to enhance the hyoscyamine production in Solanaceae species. It has been demonstrated that overexpression of TRI can increase the content of hyoscyamine and scopolamine , suggesting that PtTRI is a potential candidate for modifying the TAs biosynthetic pathway on TRI to obtain high yielding scopolamine medicinal plants.…”
Section: Discussionmentioning
confidence: 99%